Assessment of the platelet parameters and serum butyrylcholinesterase activity in type 1 diabetes patients with ketoacidosis. (November 2013) - Ma, Shao-Gang; Yang, Liu-Xue; Qiu, Xiao-Qiang
<x xml:space="preserve">Abstract</x> The potential roles of serum butyrylcholinesterase (BChE) activity and platelet indices in type 1 diabetes (T1D) remain uncertain. We aimed to investigate the correlation among the platelet indices, serum BChE activity, and diabetic ketoacidosis (DKA). Sixty-one T1D patients, 29 patients with DKA, and 30 age- and sex-matched controls were enrolled. Mean platelet volume (MPV), platelet distribution width (PDW), and serum BChE activity were measured and evaluated at admission and after the treatment. The serum BChE activity was significantly lower in patients with DKA at admission to the hospital compared with non-DKA and control subjects; however, plasma glucose level, HbA1c level, MPV and PDW were significantly higher. Serum BChE activity, variables related to glycemic control, and platelet parameters were higher in non-DKA patients than in controls. Serum BChE activity was correlated with the serum HCO3 level (r = 0.375, p < 0.05) and plasma glucose level (r = −0.387, p < 0.05). Receiver operating characteristic curve analyses showed no difference between serum BChE activity and the platelet parameters with respect to the ability to reflect DKA. Logistic regression showed that increased PDW can act as a risk marker for the presence of DKA. Serum BChE activity and the platelet parameters returned to normal along with the plasma glucose levels when metabolic acidosis was well controlled. Serum BChE activity and the platelet parameters were significantly correlated with DKA. Measurement of PDW can provide complementary information and a risk biomarker reflecting the presence of DKA.